PEMBENTUKAN KARAKTER MELALUI PENDEKATAN TASAWUF DALAM PERINGATAN MAULID NABI MUHAMMAD SAW - Nihayati, Nila Endah; Syafi’i, Imam; Islam, Saiful (Institut Dirosat Islamiyah Al-Amien Prenduan, 2025)
The celebration of the Prophet Muhammad's Mawlid in Indonesia has been a cultural tradition introduced since the era of Wali Songo. Mawlid Nabi is held to commemorate the birth of the Great Prophet Muhammad (PBUH). The connection between the commemoration of Mawlid Nabi and character formation is highly relevant. Research using a descriptive qualitative approach shows that the commemoration of the Prophet Muhammad's Mawlid, conducted in Tlogoargo Village, Tiris District, Probolinggo Regency, has a significant influence on the character development of the village community. This celebration is usually carried out through various events such as religious lectures, competitions, and storytelling about the life of Prophet Muhammad from birth to his passing. The celebration, which is accompanied by various activities, provides valuable lessons on how to show respect, love, and honesty in social life, as well as in the context of the nation and state.